Laparoscopic management of cesarean scar pregnancy with isthmocele repair using Rahman’s classification and surgical technique: a case report - Rahman, Hafeez; Farhan, Sonia; Taniya, Ayesha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
The global increase in caesarean section (CS) rates has resulted in a higher incidence of caesarean scar-related complications such as uterine niche, isthmocele, and caesarean scar pregnancy (CSP). Existing classification systems focus on when to operate rather than how to perform precise surgical repair. We present a case of a 32-year-old woman with a 5-week caesarean scar pregnancy associated with a large isthmocele, diagnosed by transvaginal ultrasound showing a 20×15 mm scar defect with a myometrial thickness of 2 mm. She underwent laparoscopic evacuation of the scar pregnancy followed by isthmocele repair based on Rahman’s classification and surgical technique. Rahman’s classification and surgical technique provide a structured approach that addresses both anatomical defects and abnormal mucosa. While this case shows a positive clinical outcome, more validation from deeper research is required before definitive conclusions on recurrence reduction or fertility outcomes can be drawn.